COOLMOS/sup TM/-a new milestone in high voltage power MOS - Lorenz, Leo; Deboy, Gerald; Knapp, A; März, Martin (Symposium on Power Semiconductor Devices and ICs, 2003)
Recently, a new technology for high voltage power MOSFETs has been introduced: the CoolMOS/sup TM/. Based on the new device concept of charge compensation, the R/sub DS(on)/ area product for e.g. 600 V transistors has been reduced by a factor of 5. The devices show no bipolar current contribution like the well known tail current observed during the turn-off phase of IGBTs. CoolMOS/sup TM/ virtually combines the low switching losses of a MOSFET with the on-state losses of an IGBT. Furthermore, the dependence of R/sub DS(on)/ on the breakdown voltage has been redefined. The more than square-law dependence in the case of standard MOSFET has been broken and a linear voltage dependence achieved. This opens the way to new fields of application even without avalanche operation. System miniaturization, higher switching frequencies, lower circuit parasitics, higher efficiency, and reduced system costs are pointing the way towards future developments. Not only has the new technology achieved breakthrough at reduced R/sub DS(on)/ values, but new benchmarks have also been set for the device capacitances. Due to chip shrinkage and a novel internal structure, the technology shows both a very small input capacitance and a strongly nonlinear output capacitance. The drastically lower gate charge facilitates and reduces the cost of controllability, and the smaller feedback capacitance reduces the dynamic losses. With this new technology, the minimum R/sub DS(on)/ values in all packages are being redefined in the important 600-1000 V categories.<br